2020
DOI: 10.1007/s10853-020-04662-y
|View full text |Cite
|
Sign up to set email alerts
|

A versatile route to edge-specific modifications to pristine graphene by electrophilic aromatic substitution

Abstract: This work presents a general method for producing edge-modified graphene using electrophilic aromatic substitution. Five types of edge-modified graphene were created from graphene/graphite nanoplatelets sourced commercially and produced by ultrasonic exfoliation of graphite in N-methyl-2-pyrrolidone. In contrast to published methods based on Friedel-Crafts acylation, this method does not introduce a carbonyl group that may retard electron transfer between the graphene sheet and its pendant groups. Graphene sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…7b). 137 Due to the reactivity of thiol groups, edge localization was visualized by attaching gold nanoparticles on the graphene-SH. 137…”
Section: Edge Selective Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…7b). 137 Due to the reactivity of thiol groups, edge localization was visualized by attaching gold nanoparticles on the graphene-SH. 137…”
Section: Edge Selective Derivatizationmentioning
confidence: 99%
“…136 Shellard and co-workers reported electrophilic aromatic substitution as an alternative method for designing edge-thiolated graphene. 137 The experimental process involves the chlorosulphonation of graphene sheets, followed by reduction into thiol (–SH) moieties, which was further attached with allyl mannoside via radical addition reaction to create glycographene for biomedical applications (Fig. 7b).…”
Section: Covalent Modification Of Go and Rgomentioning
confidence: 99%
“…48 It has been reported that the characteristic peaks of sulfur-related functional groups are usually less pronounced in the infrared spectrum. 49 Here, although there are no obvious characteristic stretching signals assigned to S-H in the region of 2500-2600 cm À1 , 44,47,50 a weak peak attributed to the C-SH bending vibration can still be observed at 797 cm À1 . 43,47,51 The new presence of the characteristic peaks to thiophenol groups in the infrared spectrum of TP-Gr can preliminarily confirm the successful grafting of thiophenol groups onto the graphene.…”
Section: Resultsmentioning
confidence: 93%
“…The absorption at about 1580 cm -1 (G band) is related to the vibration of sp 2hybridized carbon atom known as graphite band, and the D band at around 1340 cm -1 is correlated with the disorder sp 3 -hybridized carbon know as non-graphitic band. The disorder degree of carbon structure is usually evaluated by the intensity ratio I D /I G [42]. The value of I D /I G of Vulcan @ XC-72 is much greater than that of OMC, indicating a lower graphitization degree in Vulcan @ XC-72.…”
Section: Ptco/omc Catalyst Investigationmentioning
confidence: 99%